The law of the iterated logarithm for exchangeable random variables - Hu-Ming Zhang; Robert L. Taylor (International Journal of Mathematics and Mathematical Sciences)
In this note, necessary and sufficient conditions for laws of the iterated logarithm are developed for exchangeable random variables.